A study of pathway of care among persons with mental illness attending a tertiary care centre in Hyderabad - Divya Meghana Sreevaram; M Vijay Kumar; S Sireesha Srinivasa Rao (Telangana Journal of Psychiatry, 2020)
Background: Persons with mental illness usually do not visit the mental health facility first. Instead they approach faith healers and other alternative systems. Only when the condition becomes worse, do they seek psychiatrist consultation leading to delay in treatment. Materials and Methods: A cross sectional study was conducted to understand the pathway of care adopted by persons with mental illness and its relationship with sociodemographic variables. In our study population, 250 patients visiting a psychiatric outpatient department of a tertiary care hospital were interviewed on a semi structured questionnaire for various services contacted by them for their mental health problems. Data was analysed using SPSS version 22. Results: The initial study sample included 258 patients, out of which 8 were excluded because of exclusion criteria. The final study sample was 250. The mean age of sample was 35.92yrs. There were 137 males and 113 females. Our study sample comprised of 66.8% aged between 20 to 40 years, 54.8% male, 57.2% were married, 67.6% were unemployed and 75.2% earn below 10000 rupees. In illness variables, 32.0% of study subjects had duration of illness 1 to 5 years, 36.8% subjects were having schizophrenia followed by mood disorders [22.8%]. 28.4% of study sample (71 out of 250) did not consult psychiatrist at all before coming to tertiary care centre out of which 8.8% consulted faith healers. Rest 71.66% of study sample consulted general practitioners, general physicians, neurologists and ayurvedic unani homeopathic doctors. Reasons given by patient’s family members for not consulting psychiatrists were ignorance about illness, financial problems, belief in superstitions, lack of availability of mental health services and stigma towards mental illness. Socio demographic factors significantly associated with delay in first consultation to psychiatrist were found to be 20 – 40yrs of age (p=0.000), female gender (0.031), illiterate (0.025), unemployment(0.001), income <10,000 (0.014), distance >100kms (0.019) and diagnosis of schizophrenia(0.000). Conclusion: Patients with mental illness seek help from nonpsychiatric physicians, faith healers, traditional, alternative systems due to lack of awareness about treatment services, long distances and due to fear of stigma about illness. It is important to sensitize general practitioners about early identification, management and referral of psychiatric disorders.